Improving the fatigue life of steel bars by using Nano-coating technology - Yasir, Ali (International Journal of Engineering and Technology, 2014)
The fatigue failure is the reason of most mechanical failure for engineering materials. This work tried using the nano-coating technique to coat the steel bars and study the effect of this coating layers on fatigue life of steel. The Zinc Oxide (ZnO) used as it cheap and available in most labs of nanotechnology. The coating process done at different time of coating to get different thickness of coating layers. The result of fatigue tests for coated samples show increased in fatigue life for samples that coated for long time (thick layer of coat), and the increasing if fatigue life may reach to 4-times of its fatigue life for un-coated samples. Keywords: Fatigue, Fatigue Life, Steel Bars, Nano-Coating Technology, ZnO Coat.